2018
DOI: 10.3390/sym11010016
|View full text |Cite
|
Sign up to set email alerts
|

Using ANFIS and BPNN Methods to Predict the Unfrozen Water Content of Saline Soil in Western Jilin, China

Abstract: : Saline soil in seasonally frozen soil areas has caused tremendous damage to engineering and the ecological environment. The unfrozen water is the main factor affecting the properties of saline soil in seasonally frozen soil area and therefore needs to be studied. However, due to the high cost of laboratory measurement of the unfrozen water content, this study focuses on using an adaptive network fuzzy inference system (ANFIS) and a back propagation neural network (BPNN) to predict the unfrozen water content … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…It demonstrates that the unfrozen water content of frozen soil is practically independent of its initial water content. This result has also been observed in other soils (e.g., Liu et al, 2019; Nagare et al, 2012; Watanabe & Wake, 2009). In contrast, other studies found that unfrozen water content depends on initial water content (Suzuki, 2004; Teng et al, 2020; Xu et al, 1987).…”
Section: Theory Of Freezing and Thawing Processes In Soilsupporting
confidence: 83%
“…It demonstrates that the unfrozen water content of frozen soil is practically independent of its initial water content. This result has also been observed in other soils (e.g., Liu et al, 2019; Nagare et al, 2012; Watanabe & Wake, 2009). In contrast, other studies found that unfrozen water content depends on initial water content (Suzuki, 2004; Teng et al, 2020; Xu et al, 1987).…”
Section: Theory Of Freezing and Thawing Processes In Soilsupporting
confidence: 83%
“…The type of membership function and number of membership functions are decided based on the variation trend of the input and output data. The types of membership functions in the ANFIS model are triangular, trapezoidal, gbell, gauss, gauss2, pi, dsig and psig [32]. In the ANFIS model, the input and output data are connected by rules with the statements by showing the relationship between the input and output data.…”
Section: Adaptive Neuro-fuzzy Interface System Modelling (Anfis)mentioning
confidence: 99%
“…Shang and Mao (2001) proposed a model based on backpropagation neural network (BPNN) to predict the empirical parameters of the SFCC of Morin Clay under different initial water content, dry density and NaCl concentration. Based on experimental data obtained by nuclear magnetic resonance, Liu et al (2018) constructed two models using adaptive network fuzzy inference system (ANFIS) and BPNN to predict the UWC of saline soil. Wang Q et al (2020) proposed a new model to predict the UWC of saline soil based on the combined weighting method and ANFIS.…”
Section: Introductionmentioning
confidence: 99%